Pembelajaran Akidah Akhlak Berbasis Multilitersi di Madrasah Aliyah Negeri 1 Mojokerto - Farida Ulvi Na’imah, Mahmudah, (Pusdikra Publishing, 2023)
This research aims to describe the implementation and obstacles in multiliteracy-based learning of moral beliefs at Madrasah Aliyah Negeri 1 Mojokerto. This research uses qualitative research with a case study approach. Data collection was carried out by means of observation, interviews and documentation. This research shows the results that multiliteracy-based learning of moral beliefs at Madrasah Aliyah Negeri 1 Mojokerto is carried out in three stages, namely planning the implementation of learning which includes preparing lesson plans by adding literacy in learning moral beliefs. Implementation of learning which includes preliminary activities, core activities and closing activities. And learning evaluation which includes knowledge assessment, which is taken from daily assignment assessments, mid-semester assessments and final semester assessments. Skills assessments are taken from observations of daily attitudes and behavior in class and outside of class. As well as assessment of attitudes taken from oral tests, practice, and students' abilities in understanding and exploring the meaning of texts they have read, writing and explaining what they have written. The obstacles in learning moral beliefs are students' lack of interest in literacy and lack of understanding, so they give different responses when learning takes place. However, teachers continue to try to provide motivation as an effort to increase students' interest through literacy programs as a forum for channeling talent in writing, and providing appreciation for teachers and students who excel, in order to attract students' interest in literacy.